Desaturation during feeding in a term neonate due to 20p duplication syndrome - Kadirvel Karthikeyan; Chandra Kumar Natarajan; Sumathisri Ramachandran (Wolters Kluwer Medknow Publications, 2021)
Background: Feeding problems are common in preterm neonates of which desaturation during direct feeding is a known entity. However, term newborns have acceptable range of fall in saturation while feeding directly. Here, we report a term newborn with dysmorphic features had desaturation during feeding. Clinical Description: A male baby born to second-degree consanguineous parents at term who was managed for transient tachypnea of newborn had fall in saturation beyond acceptable range during feeding. He had low set ears, high-arched palate, thin upper lip, clinodactyly, and anal tag. Management: The baby was subjected for thorough exploration of respiratory/gastrointestinal/neurological systems which did not reveal attributable findings. Clinical exome sequencing revealed 20p duplication. He was started on orogastric feeding and could be gradually changed to direct feeding at 4 months of age. Conclusions: This report may improve the understanding toward approach to feeding problems in term neonates and also about phenotypic features of 20 p duplication which is less reported.